The life of the Madman of Ü - DiValerio, David M. (Oxford University Press, 2016)
"The Life of the Madman of Ü tells the story of Künga Zangpo (1458-1532), a famous Tibetan Buddhist ascetic of the Kagyü sect. Having grown weary of the trials of human existence, Künga Zangpo renounced the world during his teenage years, committing himself to learning and practicing the holy Dharma as a monk. Some years later he would give up his monkhood to take on a unique tantric asceticism that entailed dressing in human remains, wandering from place to place, and provoking others to attack him physically, among other norm-overturning behaviors. It was because of this asceticism that Künga Zangpo came to be known as the Madman of Ü. David M. Divalerio translates this biography, originally written in two parts in 1494 and 1537, making accessible to a modern audience a rich depiction of religious life in fifteenth- and sixteenth-century Tibet. The book also details Künga Zangpo's many miracles, a testament to the spiritual perfection he attained. His final thirty years were spent at his monastery of Tsimar Pel, where he dispensed teachings to his numerous disciples and followers. The Life of this remarkable and controversial figure, now available in English for the first time, provides new means for understanding the tradition of the "holy madman" (smyon pa) in Tibetan Buddhism."--